Shame and Guilt in Christian Children: Interventions with Projective Techniques and Play Therapy - Thurston, Nancy (Journal of psychology and theology, 1994)
Psychotherapy issues for religiously committed clients have been explored in several recent books and articles. While these works have focused on adults, little has been written on the therapy issues of religiously committed children. Emerging research suggests that children's conceptions of God are quite different than that of adults. Moreover, due to their concrete thinking, children often find it hard to grasp theological foundations to the Christian faith (e.g., salvation by grace) that adults typically assimilate into their world view. While children generally learn of God's grace and mercy in Sunday school, it has been found that some of them nonetheless struggle deeply with issues of guilt and shame. It has been well documented that children do not have the same cognitive and language abilities as adults, and therefore require considerably different modes of psychotherapy. For latency aged and younger children, play therapy is often the treatment of choice. This article will present a case study of a Christian child who participated in a projective assessment and play therapy for healing of shame and guilt issues.